APLICACIÓN DE MÉTODOS ANTISÉPTICOS PREVIOS AL TRATAMIENTO ODONTOLÓGICO PARA LA REDUCCIÓN DE LA CARGA MICROBIANA SALIVAL - Pineda M., Martha (2000)
Sixty eight patients of UNMSM Dentistry Faculty Central Clinic, ages 15 to 65 undergoing surgical or restaurative odontologic treatment, were selected and distributed into groups to determine and compare the effect of three pre-procedures mouth rinses and the dental brushing on aerobia salivary bacteria load reduction. The results showed that 0.12% Chlorhexidine Gluconate mouth rinse reduced aerobia salivary bacteria load compared to baseline in 91.4% at 5 min, and increased its effect to 93.3% at 60 min, on the contrary Fenolic antiseptic from 73.8% at 5 min decreased its effect to 63.4% at 60 min. 5% saline solution reduced bacteria in 58.3% at 5 min and persisted in 58.6% at 60 min, the reduction for dental brushing was of 53.7% at 5 min increasing its effect to 55.4% at 60 min.